1991
DOI: 10.1063/1.857983
|View full text |Cite
|
Sign up to set email alerts
|

Period doubling in the wake of a three-dimensional cylinder

Abstract: Forced excitation of a long cylinder having a mild variation of diameter along its midspan generates period-doubled vortex formation. The onset of this localized, period-doubled response involves formation of diamond-shaped vortical structures during every other cycle of the cylinder oscillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…From the spanwise periodicity, it can be seen that the hairpin structure appears at the same spanwise location only on alternate shedding cycles. This spanwise subharmonic behavior implies a period-doubling scenario to one suggested in previous studies [19,20].…”
supporting
confidence: 69%
“…From the spanwise periodicity, it can be seen that the hairpin structure appears at the same spanwise location only on alternate shedding cycles. This spanwise subharmonic behavior implies a period-doubling scenario to one suggested in previous studies [19,20].…”
supporting
confidence: 69%
“…Period doubling has been documented at the transition to chaos or turbulence in some previous studies of fluids [Gollub et al, 1980;Rockwell et al, 1991], but no period doubling was observed in these experiments. At some locations in the wake of the cylinder successive vortices were alternately strong and weak (Figure 6a).…”
Section: Flow Past a Cylinder Located Away From The Wallmentioning
confidence: 53%
“…Vortex shedding from cylinders occurs over a wide range of Reynolds numbers (approximately 5 x 10 • to 104 according to Batchelor [1967] and Schlichting [1968]), but the process is most regular within the lower part of this range [Roshko, 1954;Gaster, 1969]. The frequency of vortex shedding, n, is given by…”
Section: Flow Past a Cylinder Located Away From The Wallmentioning
confidence: 99%
“…In Braun, Feudel & Guzdar (1998), an externally driven row of two-dimensional vortices was studied numerically, and it was determined that the flow developed chaos through a period-doubling cascade. A period-doubling of the flow behind a cylinder with a mild variation in diameter was observed in the experiments by Rockwell, Nuzzi & Magness (1991).…”
Section: Introductionmentioning
confidence: 85%